Vista [videorecording] introduccion a la lengua espanola (complete video program) - Dellinger; Donley; garci (Vista Higher Learning, 2001)
Filmed in various parts of Ecuador, the VISTAS Video Program offers 5-7 minutes of footage for each of the eighteen lessons in the VISTAS student textbook. Each module tells the continiuing story of four college students from different Spanish-speaking countries (Ecuador, Spain, Mexico and Puerto Rico) who spend a vacation break on a bud tour of the Ecuadorian countryside with the ultimate goal climbing a volcano.